c - Sachar, Louis (Amman : al-Ahliyah, 2014)
Stanley Yelnats begins a journey of self-discovery when he is sent to a juvenile detention center in Texas and suspects the motives of a warden who forces him and the other boys to dig five-foot-deep holes as punishment.
???? ?????? ?????? ???? ?????? ????? ????? ??? ?????? ??? ???? ?????? ??????? ?? ????? ???? ?? ????? ??? ?????? ???? ????? ?? ??????? ??????? ??? ??? ??? ???? ???? ????? ????? ??. - Translated by DeepL.com.
5-8
Translation of: Holes.
Title supplied by OCLC WorldCat.
Text in Arabic.
Keywords: Buried treasure -- Fiction; Friendship -- Fiction; Homeless persons -- Fiction; Juvenile delinquency -- Fiction; Arabic language materials